Analysis of Anthropogenic Seismic Noise Characteristics in Urban and Rural Areas of Bali Island, Indonesia - Urip Setiyono; Mohammad Syamsu Rosid; Prawito Prajitno; Supriyanto Rohadi; Ade Andika Saputra (Journal of Physics and Its Applications, 2026)
Seismic noise significantly affects the quality of earthquake detection data. This study analyzes the characteristics of anthropogenic seismic noise recorded at eight permanent broadband seismic stations in the urban and rural areas of Bali, Indonesia, from 2020 to 2024. Power spectral density (PSD) analysis was performed in the frequency range of 1–10 Hz. This frequency represents the noise from human activities. A comparison of the noise between the low tourist season (March) and the peak tourist season (August) was analyzed. The results show that stations in urban areas consistently have dominant frequencies up to 10 Hz with seasonal PSD increases of +1 to +6 dB, often exceeding the New High Noise Model (NHNM). In contrast, stations in rural areas recorded lower dominant frequencies (2–6 Hz) with moderate variations and, in some cases exhibited negative ΔPSD. Local geological factors played a significant role: volcanic breccias and massive lava flows dampen high-frequency noise, while loose sediments amplify anthropogenic signals. Anomalies during specific periods, when community mobility is drastically reduced, highlight the sensitivity of rural stations to changes in human activity intensity. These findings placing Bali as a natural laboratory for studying the complex interactions between human activity, geology, and seismic noise, with broad implications for seismic network design and site evaluation in tourism and densely populated areas worldwide.